Embedding Cultural Competency in First-Year Urban and Regional Planning Undergraduates. - Cozens, Paul; Turkich, Kent; Greive, Shane (Student Success v.14 n.1 p.76-81 https://doi.org/10.5204/ssj.2482, 2023)
This practice report highlights changes made to a first-year unit in an Urban and Regional Planning degree, designed to enhance students' levels of cultural competency. We briefly discuss the history of cultural competency highlighting a lack of application in the field of urban planning. We report on a practical case study where six strategies were developed to enhance students' cultural competency. We reflect on the experience of designing and delivering a unit called Diversity and Cultural Planning. The results from 38 students who completed a cultural competency survey at the start and at the end of term, revealed an increase in overall self-assessment scores of around 12%. As cities become more diverse, this practical case study highlights the need and benefits of enhancing the cultural competency of those who both teach and learn about urban planning. [Author abstract]